Integrated Medical Curriculum in Pakistani Educational Environment its Merits and Demerits - Sundas Ahmad, Shazia Inam, Tayyeba Iftikhar Mirza, Salma Zaman, Ayesha Ghassan, Mufassar Nishat (Pakistan Journal of Medical & Health Sciences, 2023)
The majority of medical school curricula have been merged both horizontally and vertically, with clinical and fundamental sciences integrating vertically. This has contributed to a more complete education. The Flexnerian curriculum is being phased out to make room for the merging of basic sciences and clinical sciences, which are now taught concurrently across the curriculum. This modification was made to allow for integration. We have developed an alternate approach of integration in which the teaching of the sciences is displayed on the vertical axis and the defined learning outcomes are depicted on the horizontal axis; this strategy is then adopted throughout all courses. We believe that it is not sufficient to merely integrate the basic and clinical sciences in the field of medicine; rather, it is vital to lay an emphasis on the importance of humanism in addition to the public health sciences. In other words, we believe that merely integrating the basic and clinical sciences in the realm of medicine is insufficient. Integration of the basic and clinical sciences, humanism, and health population into the curriculum’s vertical axis is essential not only in the early years of the programme, but throughout its entirety. This involves the use of problem- or case-based active teaching strategies in small groups. Place of Study: Rai Medical College Sargodha Study Duration: January 2022 to June 2022 Study Design: Empirical research Conclusion: In conclusion, an integrated medical curriculum has both its positive and negative aspects to consider. An integrated curriculum, on the other hand, can offer medical students with a thorough grasp of the human body, as well as improve critical thinking and foster interdisciplinary learning, provided that it is done successfully. Keywords: integrated curriculum types, sciences integration, curricular architecture and development